Neurogenetics. - Geschwind, Daniel H.; Paulson, Henry L.; Klein, Christine, 1969- (Handbook of clinical neurology, 2018)
Neurogenetics, Part II, Volume 148, the latest release in the Handbook of Clinical Neurology, provides the latest information on the genetic methodologies that are having a significant impact on the study of neurological and psychiatric disorders. Using genetic science, researchers have identified over 200 genes that cause or contribute to neurological disorders. Still an evolving field of study, defining the relationship between genes and neurological and psychiatric disorders is expected to dramatically grow in scope. Part II builds on the foundation of Part I, expanding the coverage to dementias, paroxysmal disorders, neuromuscular disorders, white matter and demyelination diseases, cerebrovascular diseases, adult psychiatric disorders and cancer and phacomatoses.